Changes to the Regulatory Definition of Climatic Loads and Impacts on Building Structures - Bannikov, D. O.; Radkevych, A. V.; Kosiachevska, S. M. (Science and Transport Progress, 2024)
Purpose. The main purpose of the publication is a qualitative and quantitative analysis of changes in climate loads associated with the introduction of the DBN V.1.2–2:2006 standard in the national regulatory framework, compared to the previous standard, as well as further changes to this standard. Methodology. To achieve this goal, both the standards for determining loads and impacts on building structures and the Amendments introduced, which provided for a number of innovations, were considered. The main emphasis is placed on the methodology for determining various types of climatic loads, including loads from the self-weight of soils, snow and wind loads, ice and wind loads, as well as the system for compiling combinations of these loads. The issue of terminology for the process of determining loads is covered. Findings. Based on the comparative analysis, it has been established that the approach to load combinations proposed in the Amendments allows obtaining higher values than all previously used approaches. The methodology for determining the load from the self-weight of soils remained unchanged. The methodology for determining snow and wind loads has been fundamentally changed. The final values of the loads are 2.5–3 times higher than the values in the previous standard. This is most evident in Sumy and Chernihiv regions of Ukraine. The methodology for determining the ice and wind load was supplemented in terms of taking into account the wind pressure in the presence of ice deposits. At the same time, the correlation with wind pressure in the absence of ice deposits is not clear enough. Originality. Changes in the methodology for determining the main types of climatic loads on building structures for the conditions of Ukraine, in particular, loads from the self-weight of soils, snow and wind loads, ice and wind loads, as well as the system for compiling combinations of these loads, were qualitatively and quantitatively assessed. Practical value. The data obtained make it possible to determine the ways and directions for further improvement and refinement of the existing methods for calculating the main climatic loads for the conditions of Ukraine.